Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2000)
Liberalisation, Privatisation and Globalisation have come to stay, though their impact is yet to be felt in many fields of activity. Industry in India has experienced its full impact and is facing the situation I consequences to the best of its ability &: strength. Though not much notice has been taken so far, it is seen that as a consequence of globalisation, a silent invasion is on, on the higher Education System in India.